Metabarcoding Analysis of Pollen Species Foraged by Osmia excavata Alfken (Hymenoptera: Megachilidae) in China - Lu, Huanhuan; Dou, Feiyue; Hao, Youjin; Li, Yue; Zhang, Ke; Zhang, Huan; Zhou, Zeyang; Zhu, Chaodong; Huang, Dunyuan; Luo, Arong (Frontiers in Ecology and Evolution, 2021)
To meet the pollination need of economic crops, Osmia excavata has been successfully used to improve the pollination efficiency of Rosaceae and Brassicaceae plants. As a widely used pollinator of economic crops, it was not found that the systematic study of flower visiting species and diversities of O. excavata stocked in China. To investigate the foraging pollen species and diversities of O. excavata, beebread from 20 experimental plots in China was collected by the trap-nesting method and analyzed by DNA meta-barcoding technology. A total of 26 pollen plants in 14 genera and 9 families were identified. Further analysis showed that the richness and abundance of the wild flowering plants in orchards and farmlands were lower than those in the nearby semi-natural habitats. The favorite pollen comes from economic crop apple and rape, and wild flowering plant Juncus interior, Rosa gymnocarpa and Rosa laevigata. Through diversity index analysis, it is found that Anhui region has the highest pollen plants diversity, while Liaoning region has the lowest. Our results can provide a basis for flower visiting species and diversities of O. excavata.